(untitled) (Olhar de Professor, 2020)
The theories developed by Piaget and Vygotsky had great influence in teacher training and debates on literacy in Brazil along the 20th century. This essay is focused on the counterpoints between these authors concerning the relationship between language and construction of the real by the child, especially regarding the differences between development and learning, and thought and language. It is understood that language allows for the communication with the other and with oneself, as it enables the materialization of our sensitivity, as well as the coding and systematization of reality; its coding goes through not only the mastering, but also by the grasping and re-creation of this linguistic code.